PENGARUH METODE PENGAKUAN PENDAPATAN TERHADAP LABA PERUSAHAAN PT. TEBING TONDONG JAYA - Selvy (CV. Armas Suan Sejahtera, 2024)
Nowadays, financial reports in companies are very necessary for both external and internal company interests. For external company purposes, financial reports are used, for example, to obtain loans from external parties. Financial reports are used as a benchmark for external parties to assess the company's financial condition. Meanwhile, for internal parties, financial reports are used by management to make decisions for activities related to the company's financial condition. Therefore, the revenue recognition method used by the company is also in the spotlight in preparing the company's financial reports, especially the profit and loss report. Because the revenue recognition method used affects the nominal sales figures in a period. The formulation of the problem in this research is whether the effect of using the income recognition method on PT company profits. Tondong Jaya Cliffs. The method used in this research is a descriptive method with research techniques including: library research, field research by means of observation, interviews, and online research. The results of the research show that the revenue recognition method used by the company has a real effect on PT company profits. Tebing Tondong Jaya and at the same time influences the company's financial reports, especially the profit and loss report. Where the company uses the cash basis method as its revenue recognition method. The advice given by the author is that companies should apply the accrual basis method in recognizing income, apart from that the profit and loss report will also be more accurate with the use of the accrual basis method